Perceptions of the acceptability and feasibility of reducing occupational sitting: Review and thematic synthesis 11 Medical and Health Sciences 1117 Public Health and Health Services - Hadgraft, N.; Brakenridge, C.; Dunstan, D.; Owen, N.; Healy, Genevieve; Lawler, S. (Biomed Central, 2018)
© 2018 The Author(s). Background: Reducing workplace sedentary behaviour (sitting) is a topic of contemporary public health and occupational health interest. Understanding workers' perspectives on the feasibility and acceptability of strategies, and barriers and facilitators to reducing workplace sitting time, can help inform the design and implementation of targeted interventions. The aim of this qualitative synthesis was to identify and synthesise the evidence on factors perceived to influence the acceptability and feasibility of reducing sitting at work, without, and with, an associated intervention component. Methods: A systematic search of the peer-reviewed literature was conducted across multiple databases in October 2017 to identify studies with a qualitative component relating to reducing workplace sitting time. Relevant data were extracted and imported into NVivo, and analysed by three of the authors by coding the results sections of papers line-by-line, with codes organised into sub-themes and then into overarching themes. Studies with and without an associated intervention were analysed separately. Results: Thirty-two studies met the inclusion criteria, 22 of which had collected qualitative data during and/or following a workplace intervention. Sample sizes ranged from five through to 71 participants. Studies predominately involved desk-based workers (28/32) and were most frequently conducted in Australia, USA or the United Kingdom (26/32). Similar themes were identified across non-intervention and intervention studies, particularly relating to barriers and facilitators to reducing workplace sitting. Predominately, work and social environment attributes were identified as barriers/facilitators, with desk-based work and work pressures influencing the perceived feasibility of reducing sitting, particularly for low-cost interventions. Support from co-workers and managers was considered a key facilitator to reducing sitting, while social norms that discouraged movement were a prominent barrier. Across all studies, some consistent perceptions of benefits to reducing sitting were identified, including improved physical health, enhanced emotional well-being and associated work-related benefits. Conclusion: Common barriers and facilitators to reducing workplace sitting time were identified across the literature, most prominently involving the social environment and job-related demands. These findings can inform the design and implementation of workplace sitting reduction strategies. To increase the generalisability of findings, further research is needed in a more diverse range of countries and industries.